Pengaruh Gaya Kepemimpinan Dan Semangat Kerja Terhadap Kinerja Pegawai Melalui Disiplin Kerja Sebagai Variabel Intervening Pada Sman 7 - Fadila Marsanda; Dori Mittra Candana; Hilda Mary (Jurnal Ekonomi dan Bisnis Digital, 2026)
The phenomenon occurring at SMAN 7 Kerinci is that employee performance is still suboptimal. This can be observed from the failure to achieve predetermined targets, resulting in fluctuations in employee performance. This condition is evident from the lack of effective leadership, low work enthusiasm, and insufficient individual work discipline, which impacts task execution and delays the completion of employee performance, leading to less than optimal outcomes. This study aims to examine the influence of leadership style and work enthusiasm on employee performance through work discipline as an intervening variable at SMAN 7 Kerinci. The study employed a saturated sampling method, where the entire population of 66 respondents was used as the sample. Data were collected through surveys and questionnaires distributed to employees, using a quantitative approach. The data analysis technique applied was Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 4.0. The results indicate a positive but non-significant effect of leadership style on work discipline at SMAN 7 Kerinci. There is a positive and significant effect of work enthusiasm on work discipline. Leadership style has a positive but non-significant effect on employee performance, whereas work enthusiasm has a positive and significant effect on employee performance. Work discipline has a negative and non-significant effect on employee performance. Leadership style and work enthusiasm negatively influence and do not mediate work discipline in affecting employee performance.